TINGKAT KETAATAN MASYARAKAT DALAM MELAKSANAKAN PROTOKOL KESEHATAN SELAMA PANDEMI COVID-19 DI KOTA SAMARINDA KALIMANTAN TIMUR - Nova Hariani; Wafif Azizah; An Nissa falaq Qurrahmah; Nur Ulmi; Olivia Yolanda Lawono; Rizka Shofiyya Ramadhani; Imam Rosadi (Jurnal Infokes, 2022)
Corona virus disease 2019 (COVID-19) is a disease that caused by the Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2). This virus attacks the human respiratory tract and accompanied by initial symptoms such as fever, cough, sore throat, even losing of sense, taste or smell. COVID-19 is still a pandemic in various countries including Indonesia so far. The Indonesian government has implemented various efforts to prevent the transmission of the virus, starting with the implementation of health protocols to maintain personal and environmental hygiene with Large-Scale Social Restrictions since the first positive cases of COVID-19 in 2020. The Samarinda City Government participated in implementing health protocols policies cover Testing, Tracing, and Treatment (3T), Large Scale Social Restrictions, and higher level of social restrictions . This study will research the level of community compliance in implementing Health protocols during the COVID-19 pandemic in Samarinda. This research was conducted through a digital survey using Googleform. The results show that Samarinda citizens has an increase on the application of health protocols as evidenced by the awareness of washing hands and using Hand sanitizer. However, in maintaining distance and self isolation, the community still does not have high awareness enough that has a potential to create new cluster by the opportunities of virus tranmission.